O problema do comércio psicofísico na gênese da filosofia crítica kantiana - Poli, Bruno Bueno (2024)
The historical problem of elucidating the factors that prompted Kant's critical turn in 1769-70 has been the subject of at least ten different theses. In this work, we aim to conduct a detailed examination of one of these theses, adopting it as our working hypothesis. Specifically, we focus on Klaus Reich’s proposal, which posits that the mind-body problem was one of the motivating factors. In the first chapter, we present the theoretical landscape from which Kant embarked. We analyze three theories, considered canonical responses to the mind-body problem in 18th-century Germany: occasionalism, pre-established harmony, and physical influx, with a specific focus on the last two. We illustrate how these theories evolved in the German context, tracing their development from Leibniz and Wolff to Knutzen, Baumgarten, and Crusius. Through this overview, in the second chapter we analyze Kant's responses to the problem, spanning from his initial work to the Dissertation. In this chapter, we present an Entwicklungsgeschichte, a methodology frequently employed in Kant-Forschung. We show not only Kant’s enduring attention to this problem but also the internal evolution of his responses, culminating in the critical turn. Within this framework, we argue that the mind body problem played a dual role, both theoretical and practical, in the critical turn of 1769-70. In the third chapter we outline ten other theses developed in secondary literature on the critical turn and position our hypothesis among them. We also scrutinize the premises of much of this literature, highlighting areas where questioning is warranted. This approach opens space for a more realistic and fruitful understanding of Kant's development